2014
DOI: 10.1016/j.actpsy.2013.10.009
|View full text |Cite
|
Sign up to set email alerts
|

Classical conditioning and pain: Conditioned analgesia and hyperalgesia

Abstract: This article reviews situations in which stimuli produce an increase or a decrease in nociceptive responses through basic associative processes and provides an associative account of such changes. Specifically, the literature suggests that cues associated with stress can produce conditioned analgesia or conditioned hyperalgesia, depending on the properties of the conditioned stimulus (e.g., contextual cues and audiovisual cues vs. gustatory and olfactory cues, respectively) and the proprieties of the unconditi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
27
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(28 citation statements)
references
References 155 publications
(217 reference statements)
0
27
0
1
Order By: Relevance
“…A reduced pain perception is a classic effect produced by a variety of acute stressors in humans and animal models (Miguez et al 2014). However, stress is reported to inhibit or exacerbate pain perception depending on the nature and/or parameters of the stressor (Butler and Finn 2009).…”
Section: Discussionmentioning
confidence: 99%
“…A reduced pain perception is a classic effect produced by a variety of acute stressors in humans and animal models (Miguez et al 2014). However, stress is reported to inhibit or exacerbate pain perception depending on the nature and/or parameters of the stressor (Butler and Finn 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, both studies used a simultaneous conditioning paradigm in which CS and US were presented at the same time. This approach excludes expectation or changes in arousal -to which shifts in pain thresholds have been attributed in other classical conditioning studies (Harvie et al 2016a;Miguez et al 2014) -as the mechanism of effect. Indeed, the simultaneous approach seems well suited to model chronic pain as the real-world CS (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Acute stress and acute stress-associated corticosterone release in rats has, by and large, been shown to inhibit nociception, while chronic stress has been linked to hyperalgesia (Imbe et al, 2006), although analgesic effects have also been repeatedly reported (reviewed in (Miguez et al, 2014). Clinically, chronic stress has also been associated with chronic pain conditions such as fibromyalgia, chronic headache, inflammatory bowel disease and tempromandibular joint pain (McEwen and Kalia, 2010).…”
Section: Introductionmentioning
confidence: 99%